Implementasi Pembelajaran Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Berfikir Kritis Siswa - Ummi Murdilah; Mira Mira; Oman Farhurohman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research examines how Problem-Based Learning (PBL) influences students' critical thinking abilities. PBL involves tackling real-world issues to enhance these skills. A quasi-experimental design with pretest-posttest control groups was applied, comparing a PBL group with a traditional learning group. Data were gathered through critical thinking assessments conducted before and after the intervention. The results showed that students taught with PBL demonstrated greater improvements in critical thinking than those in the control group. This highlights PBL as an effective approach for developing essential 21st-century skills, urging educators to integrate PBL into their teaching methods.